2019
DOI: 10.1002/awwa.1394
|View full text |Cite
|
Sign up to set email alerts
|

Are Secondary Disinfectants Performing as Intended?

Abstract: Key Takeaways In many countries, regulations do not require the use of secondary disinfectants to ensure safe drinking water. The water industry may be overly reliant on secondary disinfectants to compensate for less‐than‐ideal treatment and distribution system management. The water industry should evaluate the use of secondary disinfectants to ensure the benefits are realized and that public health goals are being met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This is commonly driven by disinfection benefits being outweighed by risks associated with potentially carcinogenic DBPs, which are of growing concern with increasing detection/identification 6,8 . An article by Speight et al 9 . calculated the contact times required to inactivate various microorganisms (assuming 0.5 mgL −1 chlorine, pH7 and 5°C), concluding that the disinfectant contact times within DWDS are likely ineffective in their inactivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is commonly driven by disinfection benefits being outweighed by risks associated with potentially carcinogenic DBPs, which are of growing concern with increasing detection/identification 6,8 . An article by Speight et al 9 . calculated the contact times required to inactivate various microorganisms (assuming 0.5 mgL −1 chlorine, pH7 and 5°C), concluding that the disinfectant contact times within DWDS are likely ineffective in their inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…These sub-lethal doses of disinfectant can then exert a selective pressure and various research studies have shown that the presence, type and concentration of disinfection impacts the planktonic bacterial composition of drinking water, enriching or decreasing certain functional genes or bacterial taxa 10 – 12 . Similarly, comparison of regulatory water sample compliance illustrated that the USA, which uses chlorine residual disinfection, had 10 times more total coliform failures than the Netherlands, which does not use a disinfection residual 9 , this is after adjusting for population, although there are other differences beside disinfection between the systems (e.g. infrastructure age, organic concentrations).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is an important determinant of drinking water quality as it affects the physical, chemical and biological processes occurring within the DWDS, including microbial growth and the rate of chlorine decay [21]. It has been suggested that the disinfection contact times within DWDS are insufficient to inactivate various microorganisms [32]. The sub-lethal doses can then exert a selective pressure which impacts the planktonic (free-living microorganisms in the bulk-water; [33,34]) and biofilm microbiomes and cell concentrations [35,36].…”
Section: Introductionmentioning
confidence: 99%